2018
DOI: 10.3390/cancers10110448
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the MYC Oncogene in Burkitt Lymphoma through HSP90 Inhibition

Abstract: Overexpression of the MYC oncogene is a key feature of many human malignancies including Burkitt lymphoma. While MYC is widely regarded to be a promising therapeutic target, a clinically effective MYC inhibitor is still elusive. Here, we report an alternative strategy, targeting MYC indirectly through inhibition of the HSP90 machinery. We found that inhibition of HSP90 function reduces MYC expression in human Burkitt lymphoma through suppression of MYC transcription and destabilization of MYC protein, thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…HSP90 family chaperones were most often discussed in the context of cancer as some of HSP90’s known substrates are oncogenic protein kinases such as SRC, FAK, MET, EGFR, HER2 [ 145 , 146 , 147 ] as well as the telomerase [ 148 ] and the other main oncogenic drivers. These are supported either indirectly, as KRAS in the context of lung cancer [ 149 ], or as direct client proteins of the HSP chaperones, as CMYC in lymphomas [ 150 , 151 ] and p53 in numerous neoplasias. Interestingly, the HSP chaperone stabilization effect on mutant p53 is most likely a side effect of stalling the chaperone machinery normally supporting WT p53 on the intrinsically unstable missense p53 mutants, as described earlier in the section about TP53 mutants [ 22 , 24 , 25 ].…”
Section: Hsp Molecular Chaperonesmentioning
confidence: 99%
“…HSP90 family chaperones were most often discussed in the context of cancer as some of HSP90’s known substrates are oncogenic protein kinases such as SRC, FAK, MET, EGFR, HER2 [ 145 , 146 , 147 ] as well as the telomerase [ 148 ] and the other main oncogenic drivers. These are supported either indirectly, as KRAS in the context of lung cancer [ 149 ], or as direct client proteins of the HSP chaperones, as CMYC in lymphomas [ 150 , 151 ] and p53 in numerous neoplasias. Interestingly, the HSP chaperone stabilization effect on mutant p53 is most likely a side effect of stalling the chaperone machinery normally supporting WT p53 on the intrinsically unstable missense p53 mutants, as described earlier in the section about TP53 mutants [ 22 , 24 , 25 ].…”
Section: Hsp Molecular Chaperonesmentioning
confidence: 99%
“…In the latter category, JQ1 was the first reported compound to inhibit Myc-associated chromatin remodeling enzyme Brd4 [86], followed by novel BET inhibitors, such as ZEN-3694, which entered clinical trials and demonstrated efficacy in a variety of solid tumors and hematological malignancies, alone or in combination with several standards [87], and more recent OTX015 [88] and TEN-010 [89]. Indirect suppression of MYC transcription and destabilization of the Myc protein in human Burkitt’s lymphoma has been recently achieved by targeting the Myc-HSP90 axis with HSP90 inhibitors (i.e., 17-AAG or 17-DMAG) [90]. Moreover, indirect synthetically lethal approaches have been reported.…”
Section: Myc Targeting Approachesmentioning
confidence: 99%
“…Amidinopiperidine-based serine protease inhibitor 7 has been reported as a selective inducer of apoptosis in BL cells [17]. The functional overexpression and the pathogenetic role of the MYC proto-oncogene in BL is established [18], indicating the potential role of direct and indirect MYC inhibitors as new experimental therapies [19].Our previous research reported the antidepressant drug maprotiline 8 (Figure 1) as an anti-proliferative and pro-apoptotic agent in BL cell lines 21]. The serotonin transporter (SERT) has been identified in B-cell malignancies; subsequently antidepressants and structurally related compounds were investigated for potential antileukemia/antilymphoma activity [22].…”
mentioning
confidence: 99%
“…Amidinopiperidine-based serine protease inhibitor 7 has been reported as a selective inducer of apoptosis in BL cells [17]. The functional overexpression and the pathogenetic role of the MYC proto-oncogene in BL is established [18], indicating the potential role of direct and indirect MYC inhibitors as new experimental therapies [19].…”
mentioning
confidence: 99%
See 1 more Smart Citation